Functionally and morphologically damaged mitochondria observed in auditory cells under senescence-inducing stress - Teru Kamogashira (Nature Portfolio, 2017)
Auditory system senescence: Mitochondrial dynamics and respiration The mitochondrial morphology and physiology could influence the process of age-related hearing loss. Prof. Tatsuya Yamasoba’s research group at the University of Tokyo has examined the functional changes of mitochondria in terms of its respiratory function, membrane potential and morphology under premature senescence induced by oxidative stress in an auditory cell line. The morphological and functional mitochondrial damage were observed as the respiratory capacity deficiency and the fluctuation of the fusion/fission balance. Their results provide evidence of the fundamental interdependence between mitochondrial metabolic activity and its network structure in premature senescence process of auditory cells. This is a pioneer study to indicate the influence of mitochondrial dynamics and respiratory system on the premature senescence process of auditory cells. Further studies into inter cellular communication including cytoskeleton and nucleus can help us understand the etiology underlying age-related hearing loss.